"La valoración de los elementos de convicción en los delítos de evasión y su efecto jurídico en los autos de sobreseimiento dictados por la Unidad Judicial Penal con sede en el cantón Riobamba, durante el período de enero a septiembre del año 2014". - Cajas López, David Sebastián (2016)
In Chapter I is Framework, in which consist the objectives for which it has done the research, just as is the justification dealing with the reasons that encouraged the researcher to conduct this research legal. In Chapter II develops the theoretical framework, in which the theoretical foundation of the research work is included; this means that a detailed approach on the valuation of the items of evidence in crimes of evasion, their definition and classification, plus an analysis of the subject of crime is done, and the factors that influence the motions for dismissal and the types of conduct that may occur; likewise a study of responsibility is made by the commission of the crimes of evasion in addition to the types of items of evidence and the causes and factors of it. Moreover it has been convenient to analyze all motions for dismissal and finally the legal effects in the dismissal orders issued by the Criminal Judicial Unit based in the canton Riobamba. In Chapter III it has been raised field research and the respective methodology that has been used for the development of this research, as it has been made based on the actual information of the logical document files of the Criminal Judicial Unit with based in the canton Riobamba in order to gather information to support demonstration research and further that lead to the fulfillment of the objectives proposed in it. Finally, in Chapter Iv are set and raise the relevant conclusions and recommendations for research, especially concerning the most significant aspects that have led to the valuation of the items of evidence in crimes of evasion.